Analisa Usaha Berbasis Persentase Karkas Yang Dihasilkan Dari Berbagai Strain Dan Asal Sapi Potong (Studi Kasus Di RPH Kademangan Kabupaten Blitar) - Agus Santoso (Manajemen Agribisnis: Jurnal Agribisnis, 2019)
This study aims to determine the effect of badag on the percentage of carcass cattle from starin / different nationalities and cattle origin. The research was conducted in RPH Kademangan, Blitar regency for 4 months ie from January to April 2017. The material used was 200 head of cattle including Limmousin Peranakan Ongole (LimPO), and Simmental Peranakan Ongole (SimPO). The parameters observed were nation, age, live weight and cutting result. The analytical method used is descriptive analysis. The results showed that cattle from intensive farming (fattening) the carcass proportion of the SimPO nation (52.45%), and LimPO (51.38%). The weight of life is very significant effect on the percentage of carcass produced (P <0.05). Cattle derived from intensive farming (fattening) with the SimPO nation is more effective compared to other cattle origin and race. (R / C Ratio and B / C Ratio higher).